REPUTATION IN BUSINESS lessons for leaders. - Thomson, Stuart (Public affairs consultant) ([S.l.] : ROUTLEDGE, 2022)
A compelling mix of reputation management, crisis leadership and the role of politics in business, this book provides unique practical steps that leaders can take to protect their reputations and those of the organisations they head in an ever more open social media-led world. Although leaders increasingly recognise the vital intangible asset that reputation represents, too many do not really understand what reputation is and the steps that should be taken to build it and their corporate value. Given the range of factors depending on the organisation, each aspect of its complex reputational story needs to be unpicked if a reputation is to be built, maintained and protected. This step by-step-guide offers advice on how to develop the strategies needed to do this, provides clear lessons throughout from a range of experts - and distinctively, looks beyond the corporate sector to charities, governments, NGOs and the public sector. Boards, trustees, non-executive directors, senior management, and leaders of all types of organisations need to consider the steps that should be taken to build, maintain and defend their reputation, and that means knowing what their reputation is and the audiences that matter most to them. This book is the roadmap.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Public Relations; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Business Ethics; Corporate image; Corporations -- Public relations; Organizational effectiveness